МОДЕЛЮВАННЯ ПРИТИСКНИХ МАГНІТІВ МОБІЛЬНИХ РОБОТІВ КОЛО-ПОЛЬОВИМ МЕТОДОМ - Черно, О.О.; Герасін, О.С.; Топалов, А.М.; Стаканов, Д.К.; Гуров, А.П.; Вижол, Ю.О. (Інститут електродинаміки НАН України, Київ, 2021)
There are a list of complicated tasks need to be solved to increase the working productivity and decrease working cost in modern shipbuilding and ship repair. Good results in solving those problems are shown whether automation with varied robots implementation. The mobile robots able to move and perform given technological operations on different-spaced ferromagnetic surfaces are equipped with own control systems, movers and clamping devices. Usually, reliability and safety of such robots are in direct dependence on designers’ adequate representation of their behavior that is described by mathematical description of separate parts or the robot in the whole to correct control problem solving. The article amply considers the process of the climbing mobile robot clamping electromagnet simulation model building using the improved circle-field method on the example of BR-65/30 clamping electromagnet. The model is built on the basis of interpolated dependences of flux coupling and electromagnetic force on the magnetomotive force and the value of the air gap obtained by numerical calculations of the magnetic field. The dynamic properties of the electromagnet are investigated and a family of its traction characteristics is obtained by the developed model, which can be used for automatic control of the robot clamping device. References 25, figures 5, tables 3.